Prevalence of Plasmodium falciparum haplotypes associated with resistance to sulfadoxine–pyrimethamine and amodiaquine before and after upscaling of seasonal malaria chemoprevention in seven African countries: a genomic surveillance study. Issue 3 (March 2023) - Beshir, Khalid B; Muwanguzi, Julian; Nader, Johanna; Mansukhani, Raoul; Traore, Aliou; Gamougam, Kadidja; Ceesay, Sainey; Bazie, Thomas; Kolie, Fassou; Lamine, Mahaman M; Cairns, Matt; Snell, Paul; et al.
Summary: Background: Seasonal malaria chemoprevention is used in 13 countries in the Sahel region of Africa to prevent malaria in children younger than 5 years. Resistance of Plasmodium falciparum to seasonal malaria chemoprevention drugs across the region is a potential threat to this intervention. Methods: Between December, 2015, and March, 2016, and between December, 2017, and March, 2018, immediately following the 2015 and 2017 malaria transmission seasons, community surveys were done among children younger than 5 years and individuals aged 10–30 years in districts implementing seasonal malaria chemoprevention with sulfadoxine–pyrimethamine and amodiaquine in Burkina Faso, Chad, Guinea, Mali, Nigeria, Niger and The Gambia. Dried blood samples were collected and tested for P falciparum DNA by PCR. Resistance-associated haplotypes of the P falciparum genes crt, mdr1, dhfr, and dhps were identified by quantitative PCR and sequencing of isolates from the collected samples, and survey-weighted prevalence and prevalence ratio between the first and second surveys were estimated for each variant. Findings: 5130 (17·5%) of 29 274 samples from 2016 and 2176 (7·6%) of 28 546 samples from 2018 were positive for P falciparum on quantitative PCR. Among children younger than 5 years, parasite carriage decreased from 2844 of 14 345 samples (19·8% [95% CI 19·2–20·5]) in 2016 to 801 of 14 019 samples (5·7% [5·3–6·1]) in 2018 (prevalence ratio 0·27 [95% CI 0·24–0·31], p<0·0001). Genotyping found no consistent evidence of increasing prevalence of amodiaquine resistance-associated variants of crt and mdr1 between 2016 and 2018. The dhfr haplotype IRN (consisting of 51Ile-59Arg-108Asn) was common at both survey timepoints, but the dhps haplotype ISGEAA (431Ile-436Ser-437Gly-540Glu-581Ala-613Ala), crucial for resistance to sulfadoxine–pyrimethamine, was always rare. Parasites carrying amodiaquine resistance-associated variants of both crt and mdr1 together with dhfr IRN and dhps ISGEAA occurred in 0·05% of isolates. The emerging dhps haplotype VAGKGS (431Val-436Ala-437Gly-540Lys-581Gly-613Ser) was present in four countries. Interpretation: In seven African countries, evidence of a significant reduction in parasite carriage among children receiving seasonal malaria chemoprevention was found 2 years after intervention scale-up. Combined resistance-associated haplotypes remained rare, and seasonal malaria chemoprevention with sulfadoxine–pyrimethamine and amodiaquine is expected to retain effectiveness. The threat of future erosion of effectiveness due to dhps variant haplotypes requires further monitoring. Funding: Unitaid.